Mengenalkan Profesi Programmer untuk Anak Usia Dini Melalui Pelatihan Robotik - Muliyati, Dewi; Sabrina, Putri Marsha; Supriyani, Yuyun; Mutoharoh, Mutoharoh (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
Abstract Teachers in early childhood education have a central role in developing children’s intellectual, social and emotional skills through various activities. Early introduction of technology can improve literacy, social, math, and problem-solving skills. Programming ability is a key competency in the technological era. Problem-solving skills are also important in learning programming. To improve students’ skills and knowledge, robotics training is carried out so that it is hoped that students can produce simple tracks according to their understanding. Abstrak Guru dalam pendidikan usia dini memiliki peran sentral dalam mengembangkan keterampilan intelektual, sosial, dan emosional anak melalui berbagai aktivitas. Pengenalan teknologi sejak dini dapat meningkatkan keterampilan literasi, sosial, matematika, dan pemecahan masalah. Kemampuan pemrograman menjadi kompetensi kunci di era teknologi. Keterampilan pemecahan masalah juga penting dalam pembelajaran pemrograman. Untuk meningkatkan keterampilan dan pengetahuan peserta didik maka dilaksanakan pelatihan robotik sehingga diharapkan peserta didik dapat menghasilkan track sederhana sesuai dengan pemahaman mereka.